2022
DOI: 10.1088/1755-1315/1091/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation plan against liquefaction potential on Gumbasa Irrigation Canal around Jono Oge area after 2018 Central Sulawesi Earthquake

Abstract: Gumbasa Irrigation Area was one of the public infrastructures affected by the liquefaction and flow-slide. Restoring it to operate as before required a reconstruction plan with consideration on potential damage caused by the earthquake and liquefaction. The objective of this study was to assess the performance of the mitigation plan applied on Gumbasa Irrigation Area (canal and rice field). Two mitigation plans to be applied in the Gumbasa Irrigation Canal are evaluated, i.e., (1) implementing impermeable lini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…A pressure relief well (or drain) that provides quick removal of excess water pressure buildup. Several case studies have demonstrated the success of this type of drainage using gravel columns or vertical geocomposite drainage with relatively large diameters [8]. It has also been used to prevent "blowout" where the water pressure and vertical outflow gradient can become high, and has been incorporated in the design of flood control embankments, as in the Ejecta Potential theory which is related to the Artesian Flow Potential [11].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…A pressure relief well (or drain) that provides quick removal of excess water pressure buildup. Several case studies have demonstrated the success of this type of drainage using gravel columns or vertical geocomposite drainage with relatively large diameters [8]. It has also been used to prevent "blowout" where the water pressure and vertical outflow gradient can become high, and has been incorporated in the design of flood control embankments, as in the Ejecta Potential theory which is related to the Artesian Flow Potential [11].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Liquefaction mitigation has been discussed by several studies on the Gumbasa Canal, one of which is the use of impermeable layers [8]. Meanwhile, the influence of aquifers on liquefaction is hypothesized based on oral sources immediately after the earthquake [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the 2018 earthquake and liquefaction disaster, the Indonesian government rehabilitated and reconstructed the Gumbasa irrigation canal designed with a concrete lining. Pratama et al [7] stated that applying impermeable lining geogrid was the best option to mitigate liquefaction on the Gumbasa Irrigation Canal when considering easy and low-cost alternatives. Apart from this mitigation, the government also plans to build release wells along the Gumbasa irrigation canal to prevent reliquefaction.…”
Section: Introductionmentioning
confidence: 99%
“…Most liquefaction-caused lateral spreading happens on slopes with angles between 0.3 to 3, where the ground formed of loose sand and the water level is close to the surface [4]. The 2018 Palu Earthquake, which caused damage along canals, buildings, and the area of Gumbasa irrigation, was one of the lateral spreading and flow slide events caused by liquefaction that have occurred in Indonesia [5].…”
Section: Introductionmentioning
confidence: 99%